2003
DOI: 10.1038/sj.jp.7210867
|View full text |Cite
|
Sign up to set email alerts
|

A Population-based Study of Prognostic Factors Related to Major Disability in Very Preterm Survivors

Abstract: This study confirms the association between cystic PVL and major disability observed in other studies. Surgery and hypernatremia will be important to verify in future studies since preventive measures may be possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…Aim: In February of this year, an internal audit was conducted of the compliance with our unit's protocol for oxygen saturation alarms. Our results were in keeping with those described in the literature (1,2), the upper alarm settings were correct in 27%, the lower in 83.6%, and the saturations were within the target range 44% of the time. A teaching phase was then initiated for all staff regarding the audit results and the importance of adherence to the alarms for lowering BPD (3).…”
Section: Referencessupporting
confidence: 93%
See 2 more Smart Citations
“…Aim: In February of this year, an internal audit was conducted of the compliance with our unit's protocol for oxygen saturation alarms. Our results were in keeping with those described in the literature (1,2), the upper alarm settings were correct in 27%, the lower in 83.6%, and the saturations were within the target range 44% of the time. A teaching phase was then initiated for all staff regarding the audit results and the importance of adherence to the alarms for lowering BPD (3).…”
Section: Referencessupporting
confidence: 93%
“…Near Infrared spectroscopy can be used to assess cerebral blood flow and autoregulation. Aim: (1) To determine a normal reference range for cerebral tissue oxygenation (TOI) using near infrared spectroscopy in premature infants less than 1,500 g, (2) To determine changes in TOI with increasing postnatal age and correlate these with short term outcome (death or ultrasound abnormality). Methods: TOI was measured by spatially resolved spectroscopy (NIRO 200 Hamamatsu) in infants less than 1,500 g for 2 h a day for the first 3 days of life.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, plasma chloride concentration has also a strong correlation with plasma sodium concentration, and several retrospective investigations focused on natraemia have reported that changes in sodium levels, as well neonatal hyper- or hyponatraemia, were associated to increased risk of severe cerebral haemorrhage and cerebral palsy [2, 20]. …”
Section: Resultsmentioning
confidence: 99%
“…Lupton et al [9] reported no increase in intraventricular hemorrhage related to maximum sodium levels between 152 and 160 mmol/l, whereas Perrott et al [10] found that hypernatremia is associated with the development of major disability in infants between 22 and 30 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%